Integration of Islam and Science in Islamic Education Learning at Kedirgantaraan Vocational School, Indonesia - Firnanda, Rizky; Husnaini, M; Siga, Mu’min; Fuady, Ahmad Syauqi (Universitas Muhammadiyah Yogyakarta, 2026)
The persistent separation between religious knowledge and modern science continues to shape teaching practices in many schools, including vocational contexts where science–technology competence is central. This study investigates how Islam–science integration is enacted in Islamic Religious Education (PAI) at an aerospace-based vocational school (SMK Kedirgantaraan), focusing on the forms of integration applied, the implementation process, and the learning implications for students’ ethical–professional development. Using a qualitative case-study design, data were collected through semi-structured interviews, non-participant classroom observations, and document analysis (lesson plans, worksheets, and assessment rubrics), supported by triangulation and trustworthiness procedures. Findings indicate that integration is implemented as a deliberate pedagogical practice: PAI objectives are aligned with vocational themes such as safety culture, precision, procedural discipline, and accountability; classroom learning uses vocational case-based tasks and guided questioning to connect technical reasoning (SOPs, risk prevention) with Islamic ethical reflection (e.g., amanah, honesty, responsibility); and assessment captures students’ ability to justify decisions using both technical and moral grounds. The study contributes empirical evidence of “professional decision-centered” integration in a science-technology vocational setting.